2017
DOI: 10.1111/coa.12858
|View full text |Cite
|
Sign up to set email alerts
|

Management of pinna haematoma study (MaPHaeS): A multicentre retrospective observational study

Abstract: Where possible PH should be drained in an operating theatre. Multicentre randomized controlled trials are required to further investigate the impact of drainage technique and post-drainage management on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Management of AH is aimed at drainage of the hematoma followed by closure of dead space to prevent reaccumulation. In our study, application of a bolster dressing significantly 7 This study also found no significant difference in AH recurrence rate between initial treatment with I&D versus NA; however, this study was conducted in the United Kingdom, and 43 of their 83 cases were drained in an operating room. Their multivariate analysis showed that drainage in an operating room was associated with a lower rate of recurrence, but in our study, the most common presentation setting was the outpatient clinic.…”
Section: Discussionsupporting
confidence: 40%
See 3 more Smart Citations
“…Management of AH is aimed at drainage of the hematoma followed by closure of dead space to prevent reaccumulation. In our study, application of a bolster dressing significantly 7 This study also found no significant difference in AH recurrence rate between initial treatment with I&D versus NA; however, this study was conducted in the United Kingdom, and 43 of their 83 cases were drained in an operating room. Their multivariate analysis showed that drainage in an operating room was associated with a lower rate of recurrence, but in our study, the most common presentation setting was the outpatient clinic.…”
Section: Discussionsupporting
confidence: 40%
“…Bolster dressings are meant to immobilize the overlying tissue and provide consistent compression to prevent fluid accumulation. Previously, Vijendren et al did not find that compressive dressings reduced AH recurrence rate . This study also found no significant difference in AH recurrence rate between initial treatment with I&D versus NA; however, this study was conducted in the United Kingdom, and 43 of their 83 cases were drained in an operating room.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The most common treatment method for an auricular hematoma is drainage followed by techniques to prevent recurrence. 8 , 9 Common drainage techniques are scalpel incisions, aspiration, and then the placement of materials to remove the dead space. There is a large variety of postprocedural techniques for preventing recurrence.…”
Section: Introductionmentioning
confidence: 99%